Pengaruh Kepemimpinan dan Lingkungan Kerja Fisik terhadap Kinerja pegawai Dinas PUPR Provinsi Jambi - Hakim, Ikhwan Nul (Universitas Batanghari Jambi, 2024)
The title of this study is the influence of Leadership and Physical Work Environment on the Performance of Employees of the PUPR Service of Jambi Province. The purpose of this study is to determine and analyze the influence of Leadership and Physical Work Environment on the Performance of Employees of the PUPR Service of Jambi Province. This research is included in descriptive analysis research using quantitative methods to test the hypothesis, the sample of this research amounted to 72 people using the Slovin method to determine the size or number of samples needed with the condition of a relatively large population. Department of Pekerjaan Umum dan Penataan Ruang (PUPR). Implementation of government affairs and public services in the field of public works and public housing which functions as guidance and implementation of spatial planning, irrigation, construction, housing and residential areas. Multiple linear regression model with results Y = 77.743 + 0.396 X1 +0.354 X2 Leadership (X1) of 0.396 and Physical Work Environment (X2) of 0.354. The conclusion of this study shows that Leadership and Physical Work Environment have a positive and significant effect. So it can be interpreted that Leadership and Physical Work Environment affect employee performance by 44.2% and the rest is influenced by other variables.